2019
DOI: 10.1029/2018ja026176
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Fractional Hop Whistler Rate Observed by the Low‐Altitude Satellite DEMETER at the End of the Solar Cycle 23

Abstract: For the first time an evaluation of the whistler rate around the Earth is performed using results from the neural network aboard the microsatellite DEMETER. It is shown that the rate of whistlers with low dispersion calculated all around the Earth as a function of longitude vary between 1 and 6 s−1 during nighttime (22.30 LT) and between 0.5 and 0.7 s−1 during daytime (10.30 LT). The whistler rate is anticorrelated with the F10.7‐cm solar flux. A decrease by 25% of the solar flux corresponds to an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Němec et al () indeed obtained higher median wave intensities during the months of high lightning activity. A more precise attempt to resolve the lightning contribution was done by Záhlava et al (), who used the data provided by the neural network for whistler detection onboard the DEMETER spacecraft (Elie et al, ; Parrot et al, ) to better distinguish various lightning activity levels at the measurement times. All these studies show that the lightning contribution is, especially during the night, nonnegligible.…”
Section: Introductionmentioning
confidence: 99%
“…Němec et al () indeed obtained higher median wave intensities during the months of high lightning activity. A more precise attempt to resolve the lightning contribution was done by Záhlava et al (), who used the data provided by the neural network for whistler detection onboard the DEMETER spacecraft (Elie et al, ; Parrot et al, ) to better distinguish various lightning activity levels at the measurement times. All these studies show that the lightning contribution is, especially during the night, nonnegligible.…”
Section: Introductionmentioning
confidence: 99%
“…The lightning activity is naturally function of many parameters as the location and the seasons. But a recent study has shown that a map of whistler activity is very different from a map of lightning activity [20]. The main point is that the whistlers with low dispersion are strongly attenuated close to the magnetic equator.…”
Section: The Whistlersmentioning
confidence: 94%
“…It is called a whistler. Onboard the low altitude satellite DEMETER, RNF is a dedicated experiment based on a neural network to count these whistlers and to classify them by dispersion with a time resolution of 0.1024 s. Details about the RNF experiment can be found in [18] [19], and [20]. Here we will consider the whistlers with low frequency dispersion, i.e., the whistlers which corresponds to waves emitted just below the satellite.…”
Section: The Whistlersmentioning
confidence: 99%
See 1 more Smart Citation
“…Zahlava et al [6] found that waves in the ionosphere were strongly related to frequency and geomagnetic latitude by analyzing the measurements from the detection of electro-magnetic emissions transmitted from spacecraft from earthquake regions. Parrot et al [7] found that for every 1 degree Celsius change in global temperature, the frequency of lightning varies by 5% to 6%. The electronic components of satellites are susceptible to damage due to the total dose effect and single-event effect of high-energy electrons.…”
Section: Introductionmentioning
confidence: 99%